Crystallization and preliminary X‐ray diffraction analysis of UspE from Escherichia coli. Issue 12 (1st December 2014) - Xu, Yongbin; Quan, Chun‐Shan; Jin, Xuanzhen; Jin, Xiaoling; Zhao, Jing; Li, Xihui; Zheng, Wei; Jin, Liming; Liu, Dedi; Fan, Shengdi; Ha, Nam‐Chul
<x xml:space="preserve">Abstract</x> Universal stress proteins (Usps) are among the most highly induced genes when bacteria are subjected to several stress conditions such as heat shock, nutrient starvation or the presence of oxidants or other stress agents. Escherichia coli has five small Usps and one tandem‐type Usp. UspE (or YdaA) is the tandem‐type Usp and consists of two Usp domains arranged in tandem. To date, the structure of UspE remains to be elucidated. To contribute to the molecular understanding of the function of the tandem‐type UspE, UspE from E. coli was overexpressed and the recombinant protein was purified using Ni–NTA affinity, Q anion‐exchange and gel‐filtration chromatography. Crystals of UspE were obtained by sitting‐drop vapour diffusion. A diffraction data set was collected to a resolution of 3.2 Å from flash‐cooled crystals. The crystals belonged to the tetragonal space group I4122 or I4322, with unit‐cell parameters a = b = 121.1, c = 241.7 Å.